Spore special issue: Population and agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2010)
With the world population expected to exceed 9 billion by 2050, much of it in the South, this timely and informative Spore special issue addresses the challenges facing the world food system. This issue covers topics such as improving food production and access and the rural challenges of ensuring food security and protecting the environment – all in the face of rapid population growth. Highlighting the promise of investment in education, training and health, and the importance of strong, well-structured agricultural policies, this issue shows how ACP countries can create a strong basis for their economic development.